Movement and stability analysis of the Beaver Creek landslide, Saskatchewan, Canada - Yoshida, R. T.; Krahn, J. (Canadian Geotechnical Journal, 1985)
This paper presents a case history of a multiblock landslide where the blocks move at varying rates along a common horizontal slip surface which follows the contact between stratified drift and underlying till. Movement measurements indicate that the blocks towards the toe move at a higher rate than blocks towards the scarp. Stability analyses show that the entire slide mass can be analyzed as a single unit as opposed to considering each block separately. This finding is compared with the analysis of other multiblock slides. The friction angle mobilized along the horizontal slip surface falls within the range of residual values measured in the laboratory. Key words: landslides, stability, analysis, translational slides, residual strength.